Expanding Horizons in Advancements of FRET Biosensing Technologies - Munazza Fatima; Naseem Abbas (Biosensors)
Förster resonance energy transfer (FRET)-based biosensors are versatile tools for obtaining insights into various biological processes. Their working principles are based on nonradiative energy transfer from donor to acceptor fluorophores. This energy transfer is responsible for a change in fluorescence intensity, which provides a basis for the detection of biomolecules. Advantageous features of FRET biosensors include their high sensitivity and specificity. Recently, there have been notable developments to extend the usage of FRET biosensors for diverse applications. In this review, we briefly summarize the state-of-the-art developments of FRET biosensors for cellular imaging, drug discovery, pathogen detection, and cancer diagnosis. Continued research on biosensor design, donor acceptor pair optimization, and integration of innovative materials can further extend the applications of FRET biosensors across health care settings.